2016
DOI: 10.1002/jcp.25348
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biological Role of α-Mangostin in Modulating Inflammatory Response Through the Activation of SIRT-1 Signaling Pathway

Abstract: Several studies have shown that xanthones obtained from Garcinia Mangostana (GM) have remarkable biological activities. α-mangostin (α-MG) is the main constituent of the fruit hull of the GM. Several findings have suggested that SIRT-1, a nuclear histone deacetylase, could influence cellular function by the inhibition of NF-kB signaling. ROS can inhibit SIRT-1 activity by initiating oxidative modifications on its cysteine residues, and suppression of SIRT-1 enhances the NF-κB signaling resulting in inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 44 publications
(54 reference statements)
2
28
2
1
Order By: Relevance
“…The overproduction of ROS inhibits SIRT-1 activity by initiating oxidative modifications on its cysteine residues, thereby enhancing NF-κB signaling resulting in inflammatory responses. As reported in a recent study, α-MG was observed to abrogate the acetylation of p65/NF-κB and NF-κB-regulated proinflammatory gene expressions, including COX-2 and iNOS, by activating SIRT-1 in the U937 cell line [67].…”
Section: Antioxidant Activitysupporting
confidence: 77%
See 1 more Smart Citation
“…The overproduction of ROS inhibits SIRT-1 activity by initiating oxidative modifications on its cysteine residues, thereby enhancing NF-κB signaling resulting in inflammatory responses. As reported in a recent study, α-MG was observed to abrogate the acetylation of p65/NF-κB and NF-κB-regulated proinflammatory gene expressions, including COX-2 and iNOS, by activating SIRT-1 in the U937 cell line [67].…”
Section: Antioxidant Activitysupporting
confidence: 77%
“…Mammary tumorigenesis↓, CYP1A1↓, CYP1A2↓, CYP1B1↓ Ex vivo mouse mammary organ culture assay [33] CYP19/aromatase activity↓ Microsomal [34] Protein expression and activity HO-1 ↑ Cerebellar granule neurons [35] Antioxidant aSMase activity↓ Enzyme derived-bovine brain [56] Making SOD, GPx, CAT recover to normal level Isoproterenol-induced myocardial infarction [38] Attenuation of inflammation NO release↓, PEG2 release↓, iNOS expression↓, COX-2 expression↓ LPS-stimulated RAW264.7 macrophage cells [61,62] Protein and mRNA expressions of COX-2↓, PEG2↓ Human breast cancer MDA-MB-231 cells [64] Direct interaction with COX-2 and iNOS Molecular modeling and docking study [65] SIRT-1↑, p65/NFκB acetylation↓, COX-2 expression↓, iNOS expression↓, NO production↓, PEG2 level↓ LPS-stimulated U937 cells [67] Induction of cell cycle arrest cyclinD1/CDK4 expression↓, p27KIP1 expression↑, cyclinE expression↓, phosphorylated Rb expression↓ direct interaction with CDK4…”
Section: Modulation Of Phase I and Ii Enzymesmentioning
confidence: 99%
“…LPS, released from the surface of the cell membrane of Gram-negative bacteria, triggers an inflammatory response and causes severe sepsis. The cellular response to LPS includes the production of ROS and other mediators, such as NO and pro-inflammatory cytokines [30,31]. Therefore, we studied the possibility of LicoC in decreasing the cellular accumulation of ROS LPS-induced.…”
Section: Discussionmentioning
confidence: 99%
“…As the most important secondary metabolite in the plant, α‐mangostin (MG) is with the highest concentration among xanthones in mangosteen and draws intensive attentions worldwide for its significant clinical potentials these years [3]. Numerous documents have validated that it possesses substantial therapeutic potentials against cancers, infections, inflammations, Alzheimer's disease, obesity, and many other diseases [4–7].…”
Section: Introductionmentioning
confidence: 99%